2020
DOI: 10.3389/fendo.2019.00890
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Influence of Thyroid Hormone on Bone Mineral Density and Body Composition in Healthy Euthyroid Women

Abstract: The objective of this study was to evaluate whether evolution of bone mineral density (BMD) is associated with the thyroid hormone profile in a cohort of euthyroid women with no other known diseases within 1 year. Methods: This was a prospective cohort study conducted at the University of Campinas, Brazil. We used a database with 52 women aged 20-39 who were followed for 1 year in a family planning outpatient clinic. The inclusion criteria were body mass index (BMI) <30 kg/m 2 , no known diseases/medication us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…Fifty-four studies were also discarded because the full-text was not available. The full-text of the remaining 487 reports was assessed for eligibility: 353 studies were excluded, leaving 134 for inclusion in the systematic review [ 20 22 , 25 , 52 181 ]. All included studies were in English or French.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-four studies were also discarded because the full-text was not available. The full-text of the remaining 487 reports was assessed for eligibility: 353 studies were excluded, leaving 134 for inclusion in the systematic review [ 20 22 , 25 , 52 181 ]. All included studies were in English or French.…”
Section: Resultsmentioning
confidence: 99%
“…The kappa statistic was 0.82, displaying a strong inter-reviewer agreement for the full-text selection. Finally, 121 studies were included in the meta-analysis [ 20 22 , 25 , 52 153 , 163 167 , 169 , 171 – 173 , 175 , 177 181 ]: 13 [ 154 162 , 168 , 170 , 174 , 176 ] were excluded because data was missing, could not be transformed, or could not be obtained from corresponding authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BMI was positively associated with basal TSH secretion in healthy individuals, but not with pulsatile or total TSH secretion, and a higher BMI was associated with a delay in the nocturnal onset of the TSH surge in 117 healthy subjects with a mean age of 43 (range 22–77) years and a mean BMI of 26.8 (range 18.3–39.4) kg/m 2 ( 23 ). In contrast, TSH levels were not different between a small group of overweight women ( N =22) and women with normal weight ( N =30) ( 75 ).…”
Section: Sources Of Within-person Variation In Tsh Levelsmentioning
confidence: 95%
“… 35 However, other studies revealed no correlations between thyroid hormones and BMD in young euthyroid women. 36 Vendrami et al 37 found that TSH and FT4 had no correlations with BMD at any site in euthyroid postmenopausal women. This study showed no correlations of FT3, FT4, TSH, or FT3/FT4 with BMC and BMD of the lumbar spine and femur.…”
Section: Discussionmentioning
confidence: 98%